Executive functioning: A mediator between sensory processing and behaviour in autism spectrum disorder - Fernandez-Prieto, Montse (2021)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by impairments in social interaction, executive functioning, sensory-perceptual abilities and behaviour, such as anxious/depressed states, attention problems, aggression, or somatic complains. However, the dynamic relationship between these dimensions remains to be addressed. Therefore, we explored the link between executive functions, sensory processing and behaviour in 79 children and adolescents with ASD. Results showed significant associations between all dimensions-executive functions, sensory processing and behaviour. Furthermore, using structural equation modelling methods, we observed a mediation effect of executive functioning, specifically the domain pertaining to emotion regulation and control, and in the relationship between sensory processing abnormalities and behavioural problems. We discuss the importance of emotion regulation as a mediator between sensory processing and behavioural impairments and its impact in social competence in ASD.